Experiences of family members of patients with colostomies and expectations about professional intervention - Augusto Ferreira-Umpiérrez; Zoraida Fort-Fort (Universidade de São Paulo, 2014)
OBJECTIVE: the objective was to understand the experience of a group of family members of patients with colostomies, revealing their expectations regarding the intervention of health professionals.METHOD: qualitative research, with the social phenomenological approach of Alfred Schütz, conducted in Montevideo in 2012; twelve family members of patients with colostomies participated, from an ostomy service of a health institution.RESULTS: the following categories were identified: family ties, trust in the health care team, the nurse as the articulator of the process, the desire to humanize care, and adaptation to new family life.CONCLUSIONS: knowing the experience and expectations of the families of colostomy patients was achieved, emphasizing the previous family relationships to build upon them, and the trust in the health team, emphasizing the nurse as articulator of the process. Expectations focused on the desire for humanized care, enhancing adaptation of the nuclear family to the new way of life, restoring and enhancing its strengths, and collaborating in overcoming its weaknesses.